Evidence based rehabilitation after hip arthroplasty. Issue 2 (December 2020) - Colibazzi, Virginia; Coladonato, Adriano; Zanazzo, Milco; Romanini, Emilio
Background: Hip arthroplasty is considered the treatment of choice to improve the quality of life of patients affected by degenerative arthritis. The post-op rehabilitation regimen, however, is still a matter of debate. The goal of this study was to perform a systematic review of the available best evidence to provide recommendations for rehabilitation after hip arthroplasty. Materials and methods: Biomedical databases were accessed to identify guidelines, systematic reviews and randomised controlled trials addressing rehabilitation after hip arthroplasty published between 2004 and 2019. Studies were selected and extracted by two independent evaluators with standardised tools. Results: 1 guideline, 8 systematic reviews and 5 randomised controlled trials were included. All included papers were organised according the available evidence of clinical course chronology both in pre- and post-operation rehabilitation up to 6 weeks and thereafter. Although the value of a rehabilitation program after hip arthroplasty is universally recognised, the exact timing and number of sessions is still unknown. A solid literature review allows us to partially answer to this question. Conclusions: Evidence-based rehabilitation recommendations are proposed according to literature research findings. Clinical practice is still somewhat dependent on dogma and traditions, highlighting the need for additional high-quality clinical studies to address areas of uncertainty.